2014
DOI: 10.1016/j.psyneuen.2014.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Plasma oxytocin concentrations following MDMA or intranasal oxytocin in humans

Abstract: MDMA (±3,4-methylenedioxymethamphetamine, ‘ecstasy’) is reportedly used recreationally because it increases feelings of sociability and interpersonal closeness. Prior work suggests that the pro-social effects of MDMA may be mediated by release of oxytocin. A direct examination of plasma levels of oxytocin after acute doses of oxytocin and MDMA, in the same individuals, would provide further evidence for the idea that MDMA produces its prosocial effects by increasing oxytocin. Fourteen healthy MDMA users partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 48 publications
4
56
0
1
Order By: Relevance
“…In 1999, Blaicher et al (34) found that the plasma concentration of oxytocin was significantly higher in both men and women 1 minute after orgasm than at baseline and would decrease after 5 minutes. In our study, the plasma levels of oxytocin doubled after drug administration as shown in other clinical investigations (35)(36)(37)(38), hence ruling out possible objections regarding the applied oxytocin dose.…”
Section: Discussionsupporting
confidence: 80%
“…In 1999, Blaicher et al (34) found that the plasma concentration of oxytocin was significantly higher in both men and women 1 minute after orgasm than at baseline and would decrease after 5 minutes. In our study, the plasma levels of oxytocin doubled after drug administration as shown in other clinical investigations (35)(36)(37)(38), hence ruling out possible objections regarding the applied oxytocin dose.…”
Section: Discussionsupporting
confidence: 80%
“…In humans, the concentrations of OT in plasma range from 1.70 to 45.0 pmol/L (Carmichael et al, 1987;Alfven, 2004;Gossen et al, 2012;Dal Monte et al, 2014;Kirkpatrick et al, 2014;Yuen et al, 2014). It is well recognized that baseline plasma OT concentrations do not vary significantly among men (2.7 ± 0.4 pmol/L), nonpregnant women (2.5 ± 0.4 pmol/L), or pregnant women before labor (2.3 ± 0.2 pmol/L).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, central infusions of OT up-regulate hypothalamic OT mRNA and increase circulating OT levels [27]. Given that circulating levels of OT are elevated by 40 or 60 min following intranasal administration in nonhuman primates [214] and humans [167,168,215] it is possible that intranasal OT is entering the circulation directly or indirectly following the release of endogenous OT into the CNS and peripheral circulation. Future studies that examine CNS levels of radiolabelled OT following intranasal administration into OT deficient mice with intact or severed vagal afferent signaling to the hindbrain will be helpful in addressing the extent to which OT enters the CNS without impacting release of endogenous OT within the CNS.…”
Section: Translational Potentialmentioning
confidence: 99%
“…Current data, however, suggest that the intranasal route of administration is not associated with unwanted side effects [220], including adverse effects on blood pressure or heart rate relative to vehicle treatment in rats [210], healthy adults [34,167,215] and pre-diabetic obese men and women [33]. In addition, chronic subcutaneous infusions of OT failed to impact systolic blood pressure [28] or heart rate [28,93] in DIO [28], db/db [28,93] or hyperlipidemic ApoE deficient mice [187].…”
Section: Translational Potentialmentioning
confidence: 99%